Literatura dla dzieci i młodzieży a oferta współczesnych wydawnictw w Bułgarii - Kristanova, Evelina (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The author presents a short history of Bulgarian children’s literature and the most important poets and writers and their books, for example Iwan Wazow, Elin Pelin, Ran Bosiłek and Angeł Karaliiczew. In the second part Evelina Kristanova writes about contemporary publishing houses in Bulgaria editing books for children like Publishing House Egmont, Publishing House PAN, Publishing House Fjut, Public Publishing House Prosweta, Gold Duck, Chermes and Bard etc. The conclusion is that there are two types of publishers, these specialised only in children’s literature and these also publishing books for adults. The author analyses their market offers for children available on the Internet pages. In result E. Kristanova proves that they are many books of the most known Bulgarian writers for children on them. One of the most popular writers is for the years Angeł Karaliiczew.